2020
DOI: 10.1136/bmjopen-2020-040543
|View full text |Cite
|
Sign up to set email alerts
|

Supporting self-management of low back pain with an internet intervention in primary care: a protocol for a randomised controlled trial of clinical and cost-effectiveness (SupportBack 2)

Abstract: IntroductionSelf-management and remaining physically active are first-line recommendations for the care of patients with low back pain (LBP). With a lifetime prevalence of up to 85%, novel approaches to support behavioural self-management are needed. Internet interventions may provide accessible support for self-management of LBP in primary care. The aim of this randomised controlled trial is to determine the clinical and cost-effectiveness of the ‘SupportBack’ internet intervention, with or without physiother… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…For this reason, physical therapists, and other providers involved with hybrid care pathways, must develop a better understanding of how these models function in real-world settings. To date, most hybrid care models described in the literature are conceptual, 16 , 26 , 27 delivered in the context of tightly controlled randomized controlled trials, 28–32 or “blended models” 33 that involve only a single provider type delivering care through telehealth or alongside a digital resource (eg, an app). 6 , 11 , 32 , 34–37 Therefore, existing examples provide little guidance on how to integrate interdisciplinary hybrid care models into “real world” health systems.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, physical therapists, and other providers involved with hybrid care pathways, must develop a better understanding of how these models function in real-world settings. To date, most hybrid care models described in the literature are conceptual, 16 , 26 , 27 delivered in the context of tightly controlled randomized controlled trials, 28–32 or “blended models” 33 that involve only a single provider type delivering care through telehealth or alongside a digital resource (eg, an app). 6 , 11 , 32 , 34–37 Therefore, existing examples provide little guidance on how to integrate interdisciplinary hybrid care models into “real world” health systems.…”
Section: Introductionmentioning
confidence: 99%
“…In a systematic review from 2017, web-based interventions were shown to hold the potential in supporting self-management strategies in LBP [ 7 ], although the heterogeneity among studies made it difficult to draw any conclusions regarding effectiveness. An ongoing study (SupportBack2) investigates an Internet intervention designed to support patients to self-manage their LBP following consultation in primary care [ 8 ]. While previous studies are targeting patients in care, massive open online courses (MOOCs) can be used targeting a wider audience.…”
Section: Introductionmentioning
confidence: 99%